Stressors and coping strategies of migrant workers diagnosed with COVID-19 in Singapore: a qualitative study. Issue 3 (19th March 2021) - Yee, Kaisin; Peh, Hui Peng; Tan, Yee Pin; Teo, Irene; Tan, Emily U Tong; Paul, Justin; Rangabashyam, Mahalakshmi; Ramalingam, Mothi Babu; Chow, Weien; Tan, Hiang Khoon
Abstract : Introduction: The health, psychological and socioeconomic vulnerabilities of low-wage migrant workers have been magnified in the COVID-19 pandemic, especially in high-income receiving countries such as Singapore. We aimed to understand migrant worker concerns and coping strategies during the COVID-19 pandemic to address these during the crisis and inform on comprehensive support needed after the crisis. Methods: In-depth semi-structured interviews were carried out with migrant workers diagnosed with COVID-19. The participants were recruited from a COVID-19 mass quarantine facility in Singapore through a purposive sampling approach. Interviews were transcribed verbatim and thematic analysis performed to derive themes in their collective experience during the crisis. Results: Three theme categories were derived from 27 interviews: migrant worker concerns during COVID-19, coping during COVID-19 and priorities after COVID-19. Major stressors in the crisis included the inability to continue providing for their families when work is disrupted, their susceptibility to infection in crowded dormitories, the shock of receiving the COVID-19 diagnosis while asymptomatic, as well as the isolating conditions of the quarantine environment. The workers coped by keeping in contact with their families, accessing healthcare, keeping updated with the news and continuing to practise their faith and religion. They looked forward to a return to normalcy after the crisis with keeping healthy and having access to healthcare as new priorities. Conclusion: We identified coping strategies employed by the workers in quarantine, many of which were made possible through the considered design of care and service delivery in mass quarantine facilities in Singapore. These can be adopted in the set-up of other mass quarantine facilities around the world to support the health and mental well-being of those quarantined. Our findings highlight the importance of targeted policy intervention for migrant workers, in areas such as housing and working environments, equitable access to healthcare, and social protection during and after this crisis.